TRANSFORMASI KEBIJAKAN MONETER SYARIAH DALAM MENGHADAPI TANTANGAN SISTEM KEUANGAN GLOBAL MODREN ISLAM BERBASIS NILAI KEADILAN - Syifwa Nurdilla Gusvi Damanik; Nurul Hikmah Pasaribu; Muhammad Rusdi Hasibuan; Muhammad Arfan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The classroom environment plays a crucial role in shaping the quality of the learning process, particularly in improving the concentration of elementary school students. Concentration in learning in children is greatly influenced by the physical and psychological conditions created within the classroom. A neat room layout, adequate lighting, and good ventilation help create a comfortable learning atmosphere with minimal distractions. Furthermore, the use of engaging learning media and the moderate placement of visual elements can strengthen students’ focus during learning activities. Positive interactions between teachers and students are also crucial in creating a supportive learning environment. Teachers who are able to manage a classroom effectively can reduce noise, regulate the pace of activities, and provide clear directions so that students can more easily maintain attention. This study aims to illustrate how elements of the classroom environment contribute to improving elementary school students’ concentration and provide practical guidance for educators in creating a conducive learning space oriented towards children’s developmental needs.